Trigonometry 7th Edition

Published by Cengage Learning
ISBN 10: 1111826854
ISBN 13: 978-1-11182-685-7

Chapter 2 - Section 2.1 - Definition II: Right Triangle Trigonometry - 2.1 Problem Set: 48

Answer

- 2

Work Step by Step

Given expression = -2 $\sin( y + 45^{\circ})$ = -2 $\sin( 45^{\circ} + 45^{\circ})$ ( replacing y with $45^{\circ}$) = -2 $\sin90^{\circ}$ = -2$ \times (1)$ ( substituting for exact value of $\sin 90^{\circ}$) = - 2
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.